(untitled) (Agora for Physical Education and Sport, 2021)
The playground is one of the places where more social interactions take place, contributing to the construction of gender in the school. This work analyzes the previous literature to delve into how gender stereotypes condition access to leisure in the recess. Recess continues to be a transmitting moment of gender stereotypes. Girls (and some minority boys) are less active and their leisure opportunities on the playground are more limited. Teachers, group formation, symbolic games, clothing or language are some agents that transmit stereotypes. It concludes with guidelines to promote gender equality and active leisure organized in physical measures, such as the division of zones with clearly visible different purposes; social, such as the awareness of students and teachers about gender inequalities in the playground, and organizational, such as establishing shifts of use of materials and infrastructure.